Окремі проблеми кримінально-правового регулювання в умовах воєнного стану у контексті відновлення правопорядку на деокупованих територіях України - Шевчук, Т. А.; Shevchuk, T. A.; Шевчук Тетяна Анатоліївна (Вісник Кримінологічної Асоціації України. – 2023. – № 2 (29). – С. 312-321, 2023)
Виокремлено ряд проблемних питань, що виникають у теоретичній площині науки кримінального права та правозастосовчій діяльності у зв’язку з змінами, що були внесені до КК України в умовах дії правового режиму воєнного стану. Підсумовано, що досягнення високої якості закону про кримінальну відповідальність можливе лише при суворому дотриманні правил, прийомів та засобів законодавчої техніки його побудови, що являється основою недопущення розбалансування системи всього кримінального законодавства України.

In the conditions of martial law and repulsion of the armed aggression of the Russian Federation against Ukraine, a critically important direction is to ensure a high level of regulatory and legal support for the activities of the subjects of combating crime in strict accordance with the tasks set within the framework of the legal policy of the state in its criminological and criminal law dimensions. The legislator amended the Criminal Code of Ukraine after the introduction of the legal regime of martial law in Ukraine, to ensure the constitutional order, territorial integrity, peace, protection of fundamental human rights and freedoms, property, public order and public safety from criminally illegal encroachments by legal means. However, law enforcement practice shows some difficulties arising in connection with the application of new provisions of the law. In the publication, considering the achievements of scientists and the analysis of the practice of applying the relevant criminal law norms, several problematic issues that arise in the criminal law regulation of the relevant processes are highlighted. It is summarized that the achievement of high quality of criminal law is possible only with the application of rules, techniques and means of legislative technique of its construction, the mandatory observance of which is the basis for preventing the imbalance of the system of the entire criminal legislation of Ukraine.

Выделены ряд проблемных вопросов, возникающих в теоретической плоскости науки уголовного права и правоприменительной деятельности в связи с изменениями, внесенными в УК Украины в условиях действия правового режима военного положения. Подытожено, что достижение высокого качества закона об уголовной ответственности возможно только при строгом соблюдении правил, приемов и средств законодательной техники его построения, что является основой недопущения разбалансирования системы всего уголовного законодательства Украины.
Specific problems of criminal law regulation under the conditions of marital state in the context of restoration of law order in the deoccupied territories of Ukraine
Keywords: протидія злочинності; воєнний стан; державна зрада; окупація; деокуповані території; правове регулювання; кримінологічне забезпечення; crime prevention; martial law; treason; occupation; de-occupied territories; legal regulation; criminological support; противодействие преступности; военное положение; государственная измена; оккупация; деоккупированные территории; правовое регулирование; криминологическое обеспечение